2016
DOI: 10.1371/journal.pone.0146380
|View full text |Cite
|
Sign up to set email alerts
|

Complete Preoperative Evaluation of Pulmonary Atresia with Ventricular Septal Defect with Multi-Detector Computed Tomography

Abstract: ObjectiveTo compare multi-detector computed tomography (MDCT) with cardiac catheterization and transthoracic echocardiography (TTE) in comprehensive evaluation of the global cardiovascular anatomy in patients with pulmonary atresia with ventricular septal defect (PA-VSD).MethodsThe clinical and imaging data of 116 patients with PA-VSD confirmed by surgery were reviewed. Using findings at surgery as the reference standard, data from MDCT, TTE and catheterization were reviewed for assessment of native pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
4
12
1
1
Order By: Relevance
“…The results showed that TTE was the least accurate modality. The low accuracy of echocardiography (85.9%) is primarily attributable to a low sensitivity (72.9%) (9) . Regarding anomalous venous return can be categorized into TAPVR and PAPVR.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that TTE was the least accurate modality. The low accuracy of echocardiography (85.9%) is primarily attributable to a low sensitivity (72.9%) (9) . Regarding anomalous venous return can be categorized into TAPVR and PAPVR.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas TTE has a limited acoustic window for the evaluation of the branch pulmonary arteries, on CTA, segmental pulmonary blood flow can be depicted clearly and is necessary for surgical planning. In a recent report by Liu et al, imaging data in 116 patients with PA and VSD, CTA was shown to be more accurate than both catheterization and TTE for MAPCA and for the identification of native pulmonary arteries (15). CT evaluation of MAPCAs should entail a precise description of location of origin, size, and presence of origin stenosis, lung segment supplied as well as the anatomic relationship to adjacent structures such as the carina, esophagus and bronchi.…”
Section: Mapcasmentioning
confidence: 99%
“…The pulmonary vascular supply in patients with MAPCAs varies regarding origin, number, size, course and the part of the lung supplied, and is thus demanding for all the health care professionals involved 10 . Cardiac catheterisation and/‐or multi row detector computed tomography can be used once the child is born to visualise the anatomy before surgery 11 . The optimal treatment for this malformation is biventricular repair with closure of the ventricular septal defect to create blood flow from the right ventricle to the pulmonary arteries through a conduit with an acceptable right ventricular pressure.…”
Section: Introductionmentioning
confidence: 99%
“…10 Cardiac catheterisation and/-or multi row detector computed tomography can be used once the child is born to visualise the anatomy before surgery. 11 The optimal treatment for this malformation is biventricular repair with closure of the ventricular septal defect to create blood flow from the right ventricle to the pulmonary arteries through a conduit with an acceptable right ventricular pressure. In order to repair the defect, initial palliative strategies, such as inserting an aorto-pulmonary shunt or a right ventricle to pulmonary artery connection, are required.…”
mentioning
confidence: 99%